Early‐Stage Glottic Carcinoma in the United States: Demographics and Treatment Choice. (19th July 2022) - Friedman, Aaron D.; Gengler, Isabelle; Altaye, Mekibib; Tabangin, Meredith E.
Abstract : Objective: Limited investigation of factors potentially contributing to treatment choice in early‐stage glottic carcinoma (EGC) has been performed with large‐scale data. The National Cancer Database (NCDB) represents >72% of all new cancer cases in the United States. We hypothesized that NCDB variables may lend insight into treatment decisions between surgery and radiation for EGC. Methods: The NCDB was queried for all cases of T1‐2 N0 M0 glottic carcinoma from 2004 to 2016. We used multivariable logistic regression analysis to examine factors associated with first‐line treatment modality: radiation therapy (RT) versus surgery. All reported odds ratios (OR) were adjusted for age, gender, race, insurance, residence in a metropolitan area, region, and facility volume. Results: 34, 991 EGC patients received treatment: 6, 687 (19%) surgery; 20, 289 (58%) RT; and 8, 015 (23%) surgery and RT. OR for receiving RT (vs. surgery alone) were >2 for: more advanced T stage cancers (OR 2.5 [95%CI: 2.3, 2.7]), treatment at non‐academic facilities (OR 2.8, [95%CI: 2.6, 3.0]), and shorter travel distances to treatment centers (OR 2.2, [95%CI: 2.0, 2.4]). Surgery was more likely with treatment in the western US, higher income, private insurance, living in a metropolitan (vs. non‐metropolitan) area, female gender, older age, and low facility volume. Hispanic ethnicity, education level, and race were not associated with treatment type in the multivariable model. Conclusion: Most patients in the NCDB receive first‐line treatment with radiation for EGC, and this decision is associated with various tumor, patient, and treatment facility characteristics. Level of Evidence: 4 Laryngoscope, 133:901–907, 2023 Abstract : Eighty‐one percent of patients with early stage glottic carcinoma are treated with radiation therapy (alone or in combination with surgery), according to the United States National Cancer Database. Radiation therapy (vs. surgery) is significantly more likely with advancing tumor stage, treatment at a non‐academic facility, shorter distance to a treatment facility, and treatment outside the Western region of the United States.